Analisis Pengaruh Pemberian Cangkang Kelapa Sawit Terhadap Nilai Parameter Batubara - Alwa MHD Tanza Al-alang; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Allied Indo Coal Jaya is a mining company engaged in coal mining located in the town of Sawahlunto, West Sumatra. The coal produced consists of various types originating from different seams. At present coal mining activities are less effective because the company does not utilize low quality coal. The low quality coal is piling up in stockpiles and is not sold because of the low quality , it is necessary to improve the quality of coal or processing so that it can be utilized. Research by this method aims for low quality coal mixed with palm shells can be used, the purpose pen mixture of palm kernel shells with coal in order to know the calories, sulfur, ash, total moisture and volatile matter and how it compares that low quality coal can be utilized. Comparison of coal blends with shells of coconut adalah 12,5gr coal: 2,5gr shell of the coconut, 12,5gr coal : 5 gr shell of coconut , 12,5gr coal: 7, 5 grams of shell of coconut , 12,5gr coal : 10gr shell coconut palm , and 12,5gr coal : 12,5gr shell of the coconut palm . Based on the results of the research of mixing coal with a shell of coconut oil can affect the quality of the coal as calorie, the levels of ash , lowering the volatile matter, and lower the sulfur from the coal.Keywords: Quality of coal, shell of coconut, calorie, ash, volatile matter